PENGARUH BUDAYA ASING TERHADAP KESADARAN KALANGAN MUDA - Noval Aris; Dewi Setyaningrum; Muhammad Aslam; Sabrina Putri; Tiara Wulan; Ahmad Fu'adin; Dadi Mulyadi Nugraha (Karimun University, 2023)
The cultural phenomenon that is happening among young people in Indonesia, they tend to imitate and adopt outside cultures excessively. This raises several questions, such as why young people imitate outside cultures, whether this will threaten local cultures and how to address this problem. The research was conducted through an online survey to 46 young respondents in Bandung City. This article explains that this incident occurred due to the influence of social media and technological advances that made outside information and trends easily accessible. On the other hand, this incident made a positive impact such as opening new views and increasing tolerance towards other cultures. However, outside cultural influences also have negative impacts such as loss of traditional values and local cultural identity. Therefore, the right approach is needed in utilizing outside cultural influences so as to increase awareness among young people without sacrificing local cultural identity. By discussing these ongoing events, this article is expected to provide a better understanding of the issue and contribute to efforts to maintain cultural diversity and encourage the development of local culture.